Analysis of Transmission Performance for Fine Pitch Interconnect - Leong H.Y.; Yap B.K.; Chin L.P.; Zuraida E.E.; Awang Mat Z. (Trans Tech Publications Ltd, 2024)
Wire bonding is the preferred interconnection in the IC packaging. Understanding the electrical performance of bonding wire as transmission line is utmost important. To date, there are very limited studies on the transmission performance of fine pitch bare bonding wire especially the insulated wires. This paper investigated the transmission performance of single bare bonding wires and insulated bonding wires with different wire material, wire diameter, bonding height and insulation thickness at high frequency. The simulation analysis shows that when the frequency increases above 15 Ghz, the effect of geometric parameters has no significant difference to the transmission performance. The thickness of the insulation between 0.1 ?m to 0.3 ?m demonstrated similar performance for return loss and insertion loss across all frequencies. 2023 Trans Tech Publications Ltd, Switzerland.